Proceedings of the 31st Annual ACM/IEEE Symposium on Logic in Computer Science 2016
DOI: 10.1145/2933575.2935308
|View full text |Cite
|
Sign up to set email alerts
|

Two-variable Logic with a Between Relation

Abstract: We study an extension of F O 2 [<], first-order logic interpreted in finite words, in which formulas are restricted to use only two variables. We adjoin to this language two-variable atomic formulas that say, 'the letter a appears between positions x and y'. This is, in a sense, the simplest property that is not expressible using only two variables.We present several logics, both first-order and temporal, that have the same expressive power, and find matching lower and upper bounds for the complexity of satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 27 publications
(46 reference statements)
1
24
0
Order By: Relevance
“…A different but related between predicate (namely a(x, y), for a ∈ A, is true if there is an a-labelled position between positions x and y) was introduced and studied in [5,6,7]. Such a predicate is not definable in FO 2 (<), the two variable fragment of first-order logic (which corresponds to the well known semigroup variety DA [12]).…”
Section: Related Workmentioning
confidence: 99%
“…A different but related between predicate (namely a(x, y), for a ∈ A, is true if there is an a-labelled position between positions x and y) was introduced and studied in [5,6,7]. Such a predicate is not definable in FO 2 (<), the two variable fragment of first-order logic (which corresponds to the well known semigroup variety DA [12]).…”
Section: Related Workmentioning
confidence: 99%
“…Those on the left are the classes of the original dot depth hierarchy of Cohen and Brzozowski [CB71]. The logics which we have introduced in [KLPS16,KLPS18] and in this paper are at top centre. They have a nonempty intersection with every level of both the hierarchies.…”
Section: Alternation Depthmentioning
confidence: 99%
“…The situation appears to be different if we bound the size of the alphabet. In an earlier paper [KLPS16], we showed that if |A| = 2, then the alternation depth of languages in A * definable in FO 2 [<, bet] is bounded above by 3. We conjecture that for any fixed alphabet A, the alternation depth is bounded above by a linear function of |A|, but this question remains open.…”
Section: Alternation Depthmentioning
confidence: 99%
“…One can also define expressively equivalent two-variable fragments of first-order logic corresponding to the classes of interval constraints, as in our earlier work [KLPS16], but we do not pursue this here.…”
Section: Sublogicsmentioning
confidence: 99%
“…In fact threshold counting can be reduced to invariant counting or to modulo counting. In our earlier paper [KLPS16], we used the first reduction as the basis for a decision procedure. Here we use the second theorem as the basis for our decision procedure.…”
Section: Expressivenessmentioning
confidence: 99%